Indicators to dengue occurrence in municipalities of western Santa Catarina, Brazil (Research, Society and Development, 2021)
Dengue fever has been a constant concern in the health area due to the endemic and viral characteristics of the disease, making it a public health problem. This study aimed to describe indicators for the occurrence of dengue in municipalities in the western region of Santa Catarina. This is a quantitative descriptive-cross-cutting research. The investigation took place in the second half of 2017 in four municipalities (Chapecó, Descanso, Pinhalzinho and São Miguel do Oeste), which had the highest rates of dengue incidence in 2016. A search was performed on secondary data in the virtual database of DataSus and the Brazilian Institute of Geography and Statistics (IBGE) for the municipalities surveyed tracking information on coverage of the Family Health Strategy, employment and unemployment rates, education, Human Development Index, basic sanitation, coverage of the sewage network, waste management, water treatment and urbanization rate. There were deficits in the sanitary sewage system and a percentage lower than expected for the evaluation of the IDEB in High School. Accelerated urbanization favors the emergence of situations that contribute to the occurrence of dengue. Indicators such as HDI, adequate coverage of the ESF can be protective and prevention factors for dengue.